70 years of activity for the pharmaceutical community in Silesia - Grażyna Janikowska; Kazimiera Klementys; Dionizy Moska; Mariola Chudzik; Piotr Klima; Małgorzata Dołowy; Piotr Brukiewicz; Lucyna Bułaś (Polish Pharmaceutical Society, 2021)
Social activity of Silesian pharmacists for the community has always been associated with the need to create branches, scientific and professional associations. In 1947 the Polish Pharmaceutical Society (PTFarm) was founded in Warsaw and the following year a branch in Cracow. This branch also included the territory of Silesia, thus the pharmaceutical community of this region became its active members. The branch of PTFarm in Silesia was established on February 11, 1951 in Katowice. In the years 1951 - 1991 it was the only pharmaceutical organization, which took care of scientific and professional development of pharmacists, as well as, a meetings place and exchange of ideas. Members of the Katowice Branch of PTFarm through persevering many years efforts influenced the establishment of the Pharmaceutical Faculty at the Silesian Medical Academy in 1971. Successive presidents were actively cooperating with scientists from this faculty continuing the statutory activities of the Society related to the development of pharmaceutical sciences. One of the directions of the years 1976 - 1992, activities of the president Dionizy Moska was the intensified action of the History of Pharmacy Section. In 1982, a Senior Club was formed at the branch, which organizes annual scientific and social meetings to this day. During the years 1992 - 2004 the president Piotr Klima the social activities expanded of the touristic and religious events, cooperation with the new created District Pharmacists Chamber in Katowice, as well as, the organization of pharmaceutical and medical fairs and graduate meetings. The years 2004 - 2017, of which the president was Kazimiera Klementys, were associated with close cooperation with the College of Postgraduate Education Study at the Faculty of Pharmacy of Medical University of Silesia and with the Silesian Pharmaceutical Chamber in the field of organization of continuous education of pharmacists. Moreover, the PTFarm Katowice started organizing the educational conferences for 6th-year students of pharmacy and teamed up with the Silesian Branch of the Polish Dermatological Society. The years 2017-2021 conducted by the president Grażyna Janikowska brought new challenges in the conferences organization for the pharmacists, who were during specialization course. The activities started by predecessors were continued. The Young Pharmacy students were engaged to participate in the projects and more closely cooperation. The world pandemic has forced the organization of scientific and training conferences online. Summarizing, all the discussed directions of the 70-year activity of the Katowice Branch of PTFarm were significantly influenced by historical, social, legal, economic and epidemiological changes.